Case report: Ultrasound-guided intrauterine biopsy and RF ablation therapy for fetal posterior neck solid tumor: first successful report - Liu, Shanshan; Luo, Qiong; Fu, Xiaofeng; Wang, Minyan; Zou, Qingguo; Wang, Licheng; Kan, Guangjuan; Si, Xing; Dong, Heqin; Lan, Xiani; Han, Yutian; Zhu, Jiang (Frontiers in Oncology, 2022)
Large fetal head and neck tumors are being increasingly identified during prenatal examination and tend to have a poor prognosis. Nevertheless, appropriate intrauterine interventions at suitable periods can improve pregnancy outcome. Ultrasound-guided puncture biopsy of the solid fetal head and neck mass and radiofrequency ablation of a portion of the tissue can clarify the tumor pathology and reduce the tumor size, respectively. These treatment methods are reproducible and associated with reduced trauma and complications.